A importância do aleitamento materno exclusivo e o contexto pandêmico da covid-19: revisão de literatura - BONITO, Elaine Cristina Souza (2023)
Introduction: Breast milk is the most complete and essential natural food for infants, as it contains beneficial nutrients to meet the newborn's metabolic needs in their first months of life. It is of great importance for the health of women, their families and society. However, in the midst of the SARSCoV2 virus pandemic scenario, proper practices are needed for the correct management of the milk offered to the baby, in order to ensure safety during breastfeeding and to prolong breastfeeding, since the prevalence rates of breastfeeding in Brazil are still much lower than recommended. Objective: To identify the importance of exclusive breastfeeding and the recommendations and challenges in the COVID19 pandemic context. Methods: Integrative, explanatory bibliographic review study, with a qualitative approach to data from the Virtual Health Library (BVS)/BIREME, with the aid of the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific databases Electronic Library Online (SciELO) and Online Medical Literature Search and Analysis System (MEDLINE). Results: 59 articles were found and after selection by inclusion and exclusion criteria, 16 articles composed this review. For the analysis, tables were assembled with the main information from the descriptors: "Exclusive Breastfeeding", 06 (six) articles; "Components of the breast milk and the importance for the baby's health", 03 (three) articles; "Importance of breastfeeding for the mother", 02 (two) articles and "Advantages of breastfeeding and the COVID19 pandemic" 05 (five) articles. Conclusion: With all the evidence of the importance of breastfeeding, it is necessary to increase the dissemination of information, aiming at increasing breastfeeding rates in Brazil, and providing more security for mothers when breastfeeding, since, in the pandemic context of COVID 19, many uncertainties have arisen. However, it is indicated to continue the practice of breastfeeding based on biosecurity of materno Milk outweigh the benefits arising from infection by the new virus.